A bigraph-based framework for specification and analysis of context-aware systems. (2016) - Cherfia, Taha Abdelmoutaleb; Belala, Faïza; Barkaoui, Kamel
Context-aware systems refer to a particular class of ubiquitous computing in which, systems are able to sense environmental information and adapt their behaviour accordantly. However, the key challenge in the ubiquitous computing lies in providing a consistent model in order to deal with the increasing complexity and variety of context-aware systems. In this paper, we present a rigorous approach based on bigraphical reactive systems for modelling the main features of context-aware systems. The proposed approach provides a clear separation between the part of the system which is affected by the context and the remaining part. Moreover, it is equipped with a domain-specific tool, so-called BigCAS-Tool, which supports the modelling and execution of context-aware systems models. BigCAS-Tool features and capabilities are illustrated through a case study of a traffic sign recognition system.